Covariance matrix reconstruction of nonclassical light generated in an on-chip optical parametric oscillator - Kögler, Roger Alfredo (2022)
The increasing development of novel quantum technologies encourages the research in nonclassical states sources, being quantum correlated light one of the main resources for several applications of quantum mechanics. Silicon based integrated systems present huge potential for the further development of optical quantum communication, as they are compatible with microelectronic devices and telecommunication band wavelengths. The current capability of low loss waveguides production plus strong nonlinear coefficients makes this platform ideal for the generation of nonclassical states. Integrated microcavities can be tailored to act as low threshold optical parametric oscillators, where intense signal and idler modes are easily excited. Due to the parametric character of the physical process responsible for these oscillations, strong correlations are expected between the generated modes. We use resonator assisted detection systems to reconstruct the covariance matrices of the generated continuous variables states in order to retrieve the full quantum description of the system. Up to our knowledge, this is the first full tomography of states generated in an integrated third order optical parametric oscillator operating above threshold.